Implementing a Strip Story (sang kyai) in Aqidah Moral Lessons to Improve Akhlakul Karimah of Students - erlin wulandari erlin (Journal of Research in Islamic Education, 2022)
The world of education in Indonesia still prioritizes cognitive intelligence, but ignores the intelligence of the heart, soul and behavior. This is where it seems that education is experiencing a discontinuity in achieving its true educational goals. The purpose of this research is (1) to find out the process of planning a strip story (Sang Kyai) in aqeedah moral lessons to improve the akhlakul karimah students at MTs Wali Songo Sukajadi, Central Lampung. (2) To find out the implementation of the strip story (Sang Kyai) in aqeedah morals lessons to improve the akhlakul karimah students at MTs Wali Songo Sukajadi Central Lampung. This study uses a qualitative approach, as an effort to provide answers to the problems that have been described, because it uses a descriptive analysis approach. Data collection techniques through observation, interviews, and documentation. The results of this study are (1) The planning of strip stories (Sang Kyai) in aqeedah morals lessons is carried out by ustadz by preparing story books to be used as material for telling stories to students. The selection of stories must be in accordance with the subject matter of aqeedah morals, for example on the subject matter of filial piety to parents, the story raised is the story of the Kyai. Ustadz makes a story framework so that when telling stories the storyline is not messy. (2) The process of implementing the strip story (Sang Kyai) the ustadz gives stories to the students. In the implementation of the storytelling method the emphasis is on cultivating the akhlakul karimah students because by listening to the stories of ustadz-ustadz about figures who have noble character at least it can be an inspiration for students to emulate good deeds so that they can become uswatun hasanah.